Induced core–shell structure and the electric properties of (K0.48Na0.52)0.95Li0.05Nb0.95Sb0.05O3 ceramics. Issue 3 (21st December 2016) - Zhou, Min; Lu, Xiaomei; Yang, Dianyuan; He, Ju; Huang, Fengzhen; Mei, Fang; Ren, Xianming; Xu, Xingyu; Li, Yang; Zhu, Jinsong
Abstract : K-Deficient samples show the core–shell grain structure, shells with accumulated K + vacancies is the predominant source for dielectric relaxation, which can also pin domain walls and block the polarization switching. Abstract : The relationship among dielectric anomaly, ferroelectric response, defects, and microstructures was established for (K0.48(1+ x ) Na0.52 )0.95 Li0.05 Nb0.95 Sb0.05 O3 ( x = 0.04, 0.00, −0.02, −0.04 and −0.08) ceramics. For x = −0.02 and −0.04, larger coercive fields and lower remnant polarizations were obtained; besides, an additional dielectric relaxation behavior was observed with the activation energy E a being about 2.19 eV and 1.92 eV, respectively. Furthermore, the grain and grain boundary contributions to the capacitance were separated using impedance spectroscopy, which, combined with back-scattering characterization, firmly indicates the core–shell structure of K-deficient samples ( x = −0.02 and −0.04). Unlike the cores, the shells possess a large amount of K + vacancies ( ). This work paves a way for regulating the fine structure and more on the electrical properties of KNN-based materials.